2010
DOI: 10.1007/s11664-010-1212-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Metal Contamination in CMOS Image Sensors by Dark-Current and Deep-Level Transient Spectroscopies

Abstract: Pixels in complementary metal-oxide-semiconductor (CMOS) image sensors (CISs) are being scaled downward toward 1.0 lm. In this context, improvements in crucial parameters such as dark current per pixel, which suffers from defects incorporated during processing, need to be achieved. Indeed, accidental metallic contamination is a critical issue that induces dark current and reduces yield. In this paper, detection and characterization of gold and tungsten implanted in CISs using dark-current and deep-level transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…McGrath et al were the first to use DCS to study defect formation and reported that the metallic impurities contaminated CCDs [40]. Domengie et al used DCS to analyze the dark current spectrum of intentionally doped metallic impurities (Au and W) CMOS image sensor [45]. They observed substantially increased dark current spectrum intensity in metal contaminated CMOS image sensor compared with that of CMOS image sensor without intentional metal contamination.…”
Section: Methodsmentioning
confidence: 99%
“…McGrath et al were the first to use DCS to study defect formation and reported that the metallic impurities contaminated CCDs [40]. Domengie et al used DCS to analyze the dark current spectrum of intentionally doped metallic impurities (Au and W) CMOS image sensor [45]. They observed substantially increased dark current spectrum intensity in metal contaminated CMOS image sensor compared with that of CMOS image sensor without intentional metal contamination.…”
Section: Methodsmentioning
confidence: 99%
“…(43) Domengie et al demonstrated the effects of DCS signals in a CMOS image sensor intentionally contaminated with metallic impurities (W and Au) and used DLTS to evaluate them. (46) They found that the DCS signal has three peaks. They measured W-and Au-related deep-level defects in the space charge region using DLTS.…”
Section: Gettering Capability Of Hydrocarbon-molecular-ion-implanted mentioning
confidence: 99%
“…Improvements in critical device performance parameters, such as dark current per pixel, which suffers from defects and accidental metallic contamination during processing, are required for manufacturing high performance CISs. 5 As a device failure analysis technique, the detection and characterization of deep-levels in CISs using dark-current and deep-level transient spectroscopies, have employed gold and tungsten implanted in the CISs to identify the deep-levels responsible for the increase in dark current. 5 More practical contamination characterization techniques, which can be implemented on the manufacturing floor, must be developed.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%